1997
DOI: 10.1046/j.1365-2443.1997.d01-308.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular properties of the proteasome activator PA28 family proteins and γ‐interferon regulation

Abstract: Background: Recent cDNA cloning of two homologous proteasome activators, PA28a and PA28b, indicated the presence of a structurally related third protein, Ki antigen, but a functional relationship between Ki antigen and the two PA28 proteins is unknown. Accumulating evidence has implicated an important role for PA28 in the major histocompatibility complex (MHC) class I-restricted antigen processing pathway. Recently, an immunomodulatory cytokine g-interferon (g-IFN) was found to increase greatly the messages fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 49 publications
7
96
1
Order By: Relevance
“…IFNg increases the levels of both mRNA and protein for PA28a and PA28b (Tanahashi et al, 1997). PA28 is localized in part on PML NBs, the punctuate number and size of the PA28 greatly increase upon IFNg treatment.…”
Section: Pa28mentioning
confidence: 97%
“…IFNg increases the levels of both mRNA and protein for PA28a and PA28b (Tanahashi et al, 1997). PA28 is localized in part on PML NBs, the punctuate number and size of the PA28 greatly increase upon IFNg treatment.…”
Section: Pa28mentioning
confidence: 97%
“…It is thought to play an important role in the production of MHC class I antigenic peptides (Groettrup et al, 1996). PA28␥, initially called "Ki antigen," is similar to PA28␣ and ␤ (Kandil et al, 1997;Tanahashi et al, 1997), but forms only homoheptamers and is mostly nuclear. Its functions are poorly characterized, but studies in mice (Murata et al, 1999;Barton et al, 2004) and flies (Masson et al, 2003) suggest a role for this complex in cell cycle progression and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, the inserts have some regulatory function. For example, REG␥ has been reported to disappear upon interferon-␥ treatment (30), raising the possibility that the REG␥ insert harbors a degradation signal. As for REG␣ and REG␤, we have observed that KEKE motifs are found in chaperonins such as hsp90 and hsp70 (20).…”
Section: Discussionmentioning
confidence: 99%